Building on the backbone of CD47-based therapy in cancer: Combination strategies, mechanisms, and future perspectives - Zi-Han Ye; Wei-Bang Yu; Mu-Yang Huang; Jun Chen; Jin-Jian Lu (Acta Pharmaceutica Sinica B, 2023)
Described as a “don't eat me” signal, CD47 becomes a vital immune checkpoint in cancer. Its interaction with signal regulatory protein alpha (SIRPα) prevents macrophage phagocytosis. In recent years, a growing body of evidences have unveiled that CD47-based combination therapy exhibits a superior anti-cancer effect. Latest clinical trials about CD47 have adopted the regimen of collaborating with other therapies or developing CD47-directed bispecific antibodies, indicating the combination strategy as a general trend of the future. In this review, clinical and preclinical cases about the current combination strategies targeting CD47 are collected, their underlying mechanisms of action are discussed, and ideas from future perspectives are shared.